Crucial Influence of the Intramolecular Hydrogen Bond on the Coordination Mode of RC(S)NHP(S)(OiPr)2 in Homoleptic Complexes with NiII. Issue 4 (11th December 2012) - Babashkina, Maria G.; Safin, Damir A.; Srebro, Monika; Kubisiak, Piotr; Mitoraj, Mariusz P.; Bolte, Michael; Garcia, Yann
Abstract: Reaction of the deprotonated N ‐thiophosphorylated thioureas RC(S)NHP(S)(O i Pr)2 [R = EtNH (HL I ), i PrNH (HL II ), Et2 N (HL III ), 2, 5‐Me2 C6 H3 NH (HL IV ), 4‐Me2 NC6 H4 NH (HL V )] with Ni II leads to complexes of the formula[NiL I–V 2 ] . The molecular structures of the complexes in the solid were elucidated by single‐crystal X‐ray diffraction analysis. In the complexes, the metal atom is found to be in a square‐planar trans ‐ N 2 S 2 ([NiL II, IV 2 ] ) environment formed by the C=S sulfur atoms and the P–N nitrogen atoms, or in a square‐planar trans ‐ S 2 S′ 2 ([NiL I, III 2 ] ) environment formed by the C=S and P=S sulfur atoms of two deprotonated ligands. Reaction of deprotonated N ‐thiophosphorylated thioureaHL V with NiCl2 leads to violet[Ni(L‐1, 3‐ N, S )2 ] or dark violet[Ni(L‐1, 5‐ S, S′ )2 ]·(CH3 )2 C=O crystals that were isolated by recrystallization from a mixture of CH2 Cl2 or acetone, respectively, and n ‐hexane. DFT calculations confirmed that the[Ni(L I, II, IV, V ‐ N, S )2 ] conformers are more stable (by 5–7 kcal/mol) than[Ni(L I, II, IV, V ‐ S, S′ )2 ], whereas[Ni(L III ‐ N, S )2 ] is less stable (by 7–9 kcal/mol) than[Ni(L III ‐ S, S′ )2 ] . The main reason for higher stability of the 1, 3‐ N, S versus 1, 5‐ S, S′ isomers is the formation of intramolecular N–H··· S=P hydrogen bonds. The same hydrogen bonds are impossible in complex[NiL III 2 ] . In solution, complex[NiL III 2 ] has revealed an exclusively 1, 5‐ S, S′ coordination, whereas compounds[NiL I, II, IV, V 2 ] reveal at least two isomers in the 1 H and 31 P{ 1 H} NMR spectra. The major species is assigned to the 1, 3‐ N, S ‐coordinated isomer, and the minor signals are assigned to the 1, 5‐ S, S′ isomer, which was confirmed by UV/Vis spectroscopic results. The electrochemical measurements reveal reversible one‐electron reduction and irreversible oxidations both assigned to ligand‐centred processes. Ligand‐based oxidation processes agree well with TD‐DFT results. Abstract : Reaction of deprotonated RC(S)NHP(S)(O i Pr)2 [R = EtNH (HL I ), i PrNH (HL II ), Et2 N (HL III ), 2, 5‐Me2 C6 H3 NH (HL IV ), 4‐Me2 NC6 H4 NH (HL V )] with Ni II leads to[NiL I–V 2 ] . The metal atom is found to be in a square‐planar trans ‐ N 2 S 2 ([NiL II, IV 2 ] ) or in a square‐planar trans ‐ S 2 S′ 2 ([NiL I, III 2 ] ) environment. Reaction ofL V with Ni II leads to[Ni(L‐1, 3‐ N, S )2 ] or[Ni(L‐1, 5‐ S, S′ )2 ]·(CH3 )2 C=O crystals.